Expanding statin use for prevention of ASCVD in Indians: Reasoned and simplified proposals - Enas, Enas A. (Indian Heart J, 2020)
Atherosclerosis, a systemic disease, is the predominant cause of cardiovascular disease (CVD) that far exceeds other causes (egs: congenital, hypertension, arrhythmia). CVD is the leading cause of mortality globally (18 million lives, including 9 million from coronary artery disease (CAD) annually).(1) The Global Burden of Disease study reported that in the year 2017, India had one of the highest mortality, most of them premature, from CVD (2.64 million, women 1.18, men 1.45) and CAD (1.54 million, women 0.62, men 0.92) in the world.(2) A systemic disease of this magnitude and impact warrants a proactive preventive strategy and not a reactive, invasive and focal approach. In this editorial, we call for a wider use of statins in Indians, explain our rationale based on risk factors and risk-enhancing factors, and present a simplified and cost effective approach to combat CVD.